Effect of Isothermal Heat Treatment on Cyclic Life of Yitria Stabilized Zirconia and Gadolinium Zirconate Thermal Barrier Coating. (2018) - Johari, A.D.; Yunus, S.M.; Biyamin, S.A.; Rahman, M.M.; Hasini, H.; Manap, A.
Abstract: The effect of isothermal heat treatment on the thermal cyclic life of yttria stabilized zirconia (YSZ) and gadolinium zirconate (GZ) thermal barrier coatings (TBCs) have been investigated. The purpose of the isothermal heat treatment is to simulate thermal exposure on the TBC in the gas turbine. Duplex YSZ TBC with YSZ as a topcoat and NiCrAly as a bondcoat and five-layered GZ TBC with GZ as the topcoat (GZ / 50 wt.%GZ+50 wt.%YSZ / YSZ / 50 wt.%YSZ+50 wt.% NiCrAly / NiCrAlY) were plasma sprayed onto Nimonic 263 substrates to a total thickness of 900µm using F4-MB gun. The isothermal heat treatment was performed at a temperature of 1100°C for 100 hours with a heating rate of 250°C/hour in an air furnace. The thermal cyclic tests were performed with the following cycle in an air furnace: heat up from 1000°C to 1200°C within 1 hour, dwell at 1200°C for 5 minutes, water quench and oven dry. The cycle is repeated until 20% spallation of the coating. Result indicates that the isothermally heat treated five-layered GZ TBC has a better cyclic life than the duplex YSZ TBC and as-sprayed GZ TBC.